Intake, Nutrient Apparent Digestibility, and Ruminal Constituents of Crossbred Dorper × Santa Inês Sheep Fed Diets with Babassu Mesocarp Flour - Osman José de Aguiar Gerude Neto; Michelle de Oliveira Maia Parente; Henrique Nunes Parente; Arnaud Azevedo Alves; Paull Andrews Carvalho dos Santos; Miguel Arcanjo Moreira Filho; Anderson de Moura Zanine; Daniele de Jesus Ferreira; Leilson Rocha Bezerra; Ruan Mourão da Silva Gomes (The Scientific World Journal)
The aim of this study was to evaluate the effect on intake, apparent digestibility, and ruminal constituents of sheep in response to the addition of increasing levels of babassu mesocarp flour (BMF) to the diet. Twenty crossbred sheep (29.17±2.23 kg) were used in a randomized complete block design. Lambs were confined for 21 days, with 16 days for diet adaptation and 5 days for data collection, in which they were fed an isonitrogenous diet (16.5±0.2 CP, DM basis) containing 70% of concentrate and 30% (DM basis) of Tifton 85 hay. Increasing levels of BMF were 0, 10, 20, and 30% (DM basis). There was a quadratic effect (P<0.05) on the DM intake, nutrients intake, and digestibility of CP and NFC. The digestibility of DM, OM, TC, and NDF decreased linearly, while EE digestibility increased linearly with increasing levels of BMF. The high NDF content presented in the chemical composition of the babassu mesocarp flour ranked the same as fibrous food, which can limit the inclusion in the diet of high production animals. So, babassu mesocarp flour is an alternative for energy source in lambs feed and can be added at levels up to 10%.